Bound for beatitude : a Thomistic study in eschatology and ethics - Hütter, Reinhard, 1958- (Thomistic ressourcement series, 2019)
Bound for Beatitude is about St. Thomas Aquinas's theology of beatitude and the journey thereto. Consequently, the work's topic is the meaning and purpose of human life embedded in that of the whole cosmos. This study is not an antiquarian exercise in the thought of some sundry medieval thinker, but an exercise of ressourcement in the philosophical and theological wisdom of one of the most profound theologians of the Catholic Church, one whom the Church has canonized, granted the title "Doctor of the Church," and for a long time regarded as the common doctor. This exercise of ressourcement takes its methodological cues from the common doctor; hence, it is an integrated exercise of philosophical, dogmatic, and moral theology. Its specific theological topic, the ultimate human end, perfect happiness, beatitude, and the journey thereto-stands at the very heart of St. Thomas's theology. Far from being passe, his theology of beatitude is of urgent pertinence as the crisis of humanity and of creation and the exile of God seems to approach its apogee. By way of a presentation, interpretation, and defense of Thomas Aquinas's doctrine of beatitude and the journey thereto, Bound for Beatitude advances an argument based on four theses: (1) The loss of a theology of beatitude has greatly impoverished contemporary theology. In order to succeed and flourish, theology must recover a sound teleological orientation. (2) In order to recover a sound teleological orientation, theology must recover metaphysics as its privileged instrument. (3) Thomas Aquinas provides a still pertinent model for how theology might achieve these goals in a metaphysically profound theology of beatitude and the beatific vision. Finally, (4) Aquinas's rich and sophisticated account of the virtues charts the journey to beatitude in a way that still has analytic force and striking relevance in the early twenty-first century